SIFAT FISIKOKIMIA LAHAN PERTANIAN MONOKULTUR PADA BEBERAPA KELAS LERENG DI DAERAH UTARA KAKI GUNUNG TALANG - Junaidi Junaidi; Mimien Harianti; Oktanis Emalinda; Herviyanti Herviyanti; Azizah R (Jurnal Solum, 2021)
The area at the foot of Mount Talang is one of the areas that excellent in agriculture, especially the cultivation of horticultural crops. In the northern area with steep slope conditions, the local community applies an intensive monoculture cropping system, this will accelerate land degradation in the long term. This study aims to examine the physicochemical properties of monoculture agricultural land in the northern foothills of Mount Talang on several slopes. This research was conducted with a survey method, soil sampling was carried out by means of purposive random sampling, on monoculture agricultural land on slopes > 45%, 25-45%, 15-25%, and 8-15% and forest as control, at a depth of 0 -20cm and 20-40cm. The results showed that the soil texture that dominates at the forest and monoculture agricultural land are dusty loam. Soil water content increases with increasing soil layer depth, soil water content in monocultures 25-45% (73.72%) is the highest. Soil volume weight ranging from 0.4-0.6 g / cm3 has the same tendency at both soil depths. The total pore space of forest land and monoculture agricultural land is a large average of 75% with high criteria. The highest soil organic C content was found in monoculture agricultural land with a slope of >45%. The pH value of H2O for all land uses was 5.15-5.29 and the pH for KCl was 4.5-5.2 for acid criteria. The cation exchange capacity was above 40 me/100g (very high criteria), the total N content was 0.8-1.6% with very high criteria, too. Based on the researchs data, the physicochemical properties of monoculture agricultural land on several slope classes matched the physiochemical conditions of the forest. The potential for land degradation is still minimal even though it is on the upper slopes of the foot of Mount Talang. However, monoculture farming while maintaining soil organic matter content must remain a priority for agricultural land management in this area.Key words: monoculture land, forest, slope, North area of foot Mount Talang